Clinical profile of idiopathic angioedema based on severity and treatment response is independent of the presence of concomitant wheals. Issue 1 (24th January 2023) - Soegiharto, Reineke; Alizadeh Aghdam, Mehran; Knulst, Andre C.; Röckmann, Heike
Abstract: Background: Idiopathic angioedema varies in disease severity and treatment response, possibly due to different pathophysiological mechanisms. The presence of wheals is an indicator for histamine‐mediated angioedema. Idiopathic angioedema patients are treated in accordance with chronic spontaneous urticaria guidelines. Little is known about treatment effectiveness in idiopathic angioedema patients without wheals in comparison to idiopathic angioedema patients with concomitant wheals. Objective: To describe the disease severity profile in patients with angioedema of unknown cause in relation to prophylactic treatment and the presence or absence of concomitant wheals. Methods: In this retrospective cohort study, all records of angioedema patients visiting the outpatient clinic of the UMC Utrecht between January 2015 and March 2020 were screened. Patients with idiopathic angioedema, including those with concomitant wheals, were included. Attack frequency, patient‐reported disease control and attack treatment as indicator for severity were analysed in relation to prophylactic treatment at follow‐up and outcomes were compared between patients with and without concomitant subordinary wheals. Results: Two hundred thirty‐six patients were included: 95% (139/236) with angioedema only and 41% (97/236) with angioedema and concomitant subordinary wheals. No prophylactic treatment was prescribed in 27% (64/236), with well‐controlled disease in 86% (25/29) of patients. Antihistamine monotherapy was used in 59% (139/236) of patients and resulted in well‐controlled disease in 68% (62/92). Add‐on treatment was prescribed in 14% (33/236) of patients, omalizumab in 9% (22/236) specifically, with complete response in 38% (6/16) of patients and low attack frequency in another 18% (3/16). Difficult‐to‐treat disease was seen in 8% (18/236), with no response to a fourfold dose of antihistamines or omalizumab. All findings were independent from the presence of concomitant wheals. Conclusion: Angioedema is well manageable in the majority of patients without prophylactic therapy or antihistamine monotherapy, but a substantial proportion does not respond to antihistamines and/or omalizumab. Treatment response was independent of the presence or absence of concomitant wheals. Abstract :